Work related musculoskeletal disorders and its association with quality of life among quarry workers in Ebonyi state, Nigeria - Stanley, Njaka (2021)
Quarry industries serve as the major sources of livelihood to over 20 million workers and their dependents in developing countries. In Nigeria, quarry account for 9% of the economic growth and 42% of the gross domestic products. Work-related musculoskeletal disorders (WRMSDs) has been recognised as a threat to the safety of the workers. This study aimed to assess the prevalence of WRMSDs, quality of life, postural changes and the factors associated with WRMSDs among the quarry workers in Ebonyi State, Nigeria. Data were collected through cross-sectional survey using self-administered questionnaires consisted of the Nordic Musculoskeletal Questionnaire, the World Health Organisation Quality of Life BREF (WHOQOLBREF) and Rapid Upper Limb Assessment (RULA). Participants were selected through systematic random sampling among those who fulfilled the inclusion criteria. Two hundred and sixty-six quarry workers (266) participated in this study with 100% response rate. The data were analysed using SPSS version 26. Descriptive statistics was used to determine the prevalence of WRMSDs, types of WRMSDs and quality of life and presented in frequencies and percentage. Simple logistic regression was used on the factors associated with WRMSDs and the quality of life and finally, those with significant association at p-value <0.25 were modelled using multiple logistic regression analysis. The result shows that majority of the respondents (89.8%) had WRMSDs with the most common being lower back pain (83.1%) and elbow pain (45.9%). About 74.1% reported dissatisfaction with their quality of life on the overall. Based on multiple logistic regression modelling, BMI, age and break time were significantly associated with WRMSDs (Adjusted OR 0.174, 95% CI 0.055,0.546, p=0.003); (Adjusted OR 1.143, 95% CI 1.066, 1.226, p<0.001); (Adjusted OR 0.945, 95% CI 0.908,0.984, p=0.006). Moreover, WRMSDs and poor work design were also significantly associated with poor quality of life among quarry workers (Adjusted OR 4.28, 95% CI 1.89, 9.7, P=0.001) and (Adjusted OR 3.22, 95% CI 1.52,6.82, P=0.002) respectively. The RULA assessment revealed that 70.8% of the participants scored 7, which requires immediate investigation and implementation of ergonomic changes. In conclusion, quarry workers in Ebonyi state Nigeria experienced high rate of WRMSDs and had poor quality of life. Therefore, appropriate ergonomic and personal measures need to be implemented to improve the safety and wellbeing of the workers at quarry industries Ebonyi state, Nigeria.